Legionella pneumophila 6S RNA optimizes intracellular multiplication - Faucher, Sébastien P; Friedlander, Gilgi; Livny, Jonathan; Margalit, Hanah; Shuman, Howard A (Proceedings of the National Academy of Sciences - PNAS, 2010)
Legionella pneumophila is a Gram-negative opportunistic human pathogen that infects and multiplies in a broad range of phagocytic protozoan and mammalian phagocytes. Based on the observation that small regulatory RNAs (sRNAs) play an important role in controlling virulence-related genes in several pathogenic bacteria, we attempted to identify sRNAs expressed by L. pneumophila. We used computational prediction followed by experimental verification to identify and characterize sRNAs encoded in the L. pneumophila genome. A 50-mer probe microarray was constructed to test the expression of predicted sRNAs in bacteria grown under a variety of conditions. This strategy successfully identified 22 expressed RNAs, out of which 6 were confirmed by northern blot and RACE. One of the identified sRNAs is highly expressed in postexponential phase, and computational prediction of its secondary structure reveals a striking similarity to the structure of 6S RNA, a widely distributed prokaryotic sRNA, known to regulate the activity of σ⁷⁰-containing RNA polymerase. A 70-mer probe microarray was used to identify genes affected by L. pneumophila 6S RNA in stationary phase. The 6S RNA positively regulates expression of genes encoding type IVB secretion system effectors, stress response genes such as groES and recA, as well as many genes involved in acquisition of nutrients and genes with unknown or hypothetical functions. Deletion of 6S RNA significantly reduced L. pneumophila intracellular multiplication in both protist and mammalian host cells, but had no detectable effect on growth in rich media.